Investigating the Reward Cycle of Play in Pigs (Sus scrofa) - Lidfors, Lena M.; Farhadi, Negar; Anderson, Claes; Zupan Šemrov, Manja (Frontiers in Animal Science, 2021)
Observations of play in animals have been suggested as a promising indicator of positive emotions and thus of positive animal welfare. However, if play can follow the proposed reward cycle concept where animals estimate and value reward differently in different phases of the cycle (anticipation, consummation and post-consummation) is unclear. To investigate if a reward cycle for play exists in growing pigs, we carried out an exploratory study where pigs were tested when they were naïve to a reward cycle test (first occasion) against when they were accustomed to going through the test after having the access to an open play arena with objects. Forty undocked pigs were housed in a weaner stable with two castrated males and two females per pen. Within each litter, we randomly selected and tested one male and one female test pig, each being tested as naïve or accustomed to the testing environment. The first week the pigs (n=20) were tested four times and regarded as naïve during the first day. After that they were regarded as accustomed, and were tested twice a week for three weeks. We observed the Behaviour of the tested pairs in three subsequent stages: (1) in a holding pen 3 min, (2) in a play arena 15 min, and (3) in their home pen 10 min. When accustomed, pigs showed more locomotor play, social interactions and standing, and a tendency of more orientation towards the play arena and exploring bars facing the play arena (i.e. reward-seeking Behaviour) in the holding pen than when they were naïve, suggesting an anticipation to enter the play arena. Performing high numbers of object play in all sessions, and for accustomed pigs more exploration and social interaction, but less locomotor play and walking in the play arena may suggest consumption of play and exploration. Finding more lying and sitting in accustomed pigs, but less standing and walking in the home pen is in line with the previous hypothesis of the post-consummatory behaviors. Our results imply that the reward cycle for play may exist in pigs and generate questions for future research.